Prophetic Approach in Building the Economic Base of the State in Medina (A Modern Historical Study) - Bukhari, Abdul Ghaffar; Gondal, Abdul Qadir Abdul Karim (Journal of Islamic and Religious Studies, 2021)
The Holy Prophet realized the importance of the economy in strengthening the power and stability of the Islamic State and established an independent market, compatible in its controls and transactions with the foundations and principles of Islamic law. He had distinct curriculum in treating these problems as he Made the economy a servant for the community after the community was serviced for the economy. This research aims to indicate the approach of the Prophet ﷺ in establishing and activating the state's economic base in Medina and highlighting the great achievements in this area in the Prophet's covenant, to the case of excellence and progress and in all aspects. The Prophet was able to put the cornerstone of a major economic revolution, and the greatness of the plan followed by the Prophet ﷺ was to address the economic problem. The first work by the Prophet ﷺ, after the construction of the mosque, was establishment of a market for Muslims, dealing on a free basis which had a significant impact on the economic monopoly of the Jews. The Prophet ﷺ put rules and general economic controls in trade markets, causing the nature of economics in the Prophetic era a moral stamp.